Taxonomic revision of Lepidura Townes, 1971 (Hymenoptera: Ichneumonidae: Mesochorinae) with the description of three new species, new distribution records and a key to the all known species - Araujo, Rodrigo O.; Vivallo, Felipe (Zootaxa, 2018)
A taxonomic review of Lepidura Townes is presented, with three new species described. The following species are recognized: L. abbreviata Dasch, L. callaina Dasch, L. collaris Townes, L. improcera Dasch, L. mallecoensis Dasch, L. olivacea Dasch, L. rubicunda Dasch, L. tenebrosa Dasch, L. tuberosa Dasch, L. variegata Dasch, L. viridis Dasch, L. nigricephala sp. nov., L. patagonica sp. nov. and L. seminitida sp. nov. Species are restricted to Southern South America, occurring in the Andean biogeographic zone. New occurrence records and distribution maps are provided for all species, as well as diagnoses based on type specimens. In addition, an updated key for all species is provided.